Measurement of the energy distribution of electrons escaping minimum-B ECR plasmas. (20th February 2018) - Izotov, I; Tarvainen, O; Skalyga, V; Mansfeld, D; Kalvas, T; Koivisto, H; Kronholm, R
Abstract: The measurement of the electron energy distribution (EED) of electrons escaping axially from a minimum-B electron cyclotron resonance ion source (ECRIS) is reported. The experimental data were recorded with a room-temperature 14 GHz ECRIS at the JYFL accelerator laboratory. The electrons escaping through the extraction mirror of the ion source were detected with a secondary electron amplifier placed downstream from a dipole magnet serving as an electron spectrometer with 500 eV resolution. It was discovered that the EED in the range of 5–250 keV is strongly non-Maxwellian and exhibits several local maxima below 20 keV energy. It was observed that the most influential ion source operating parameter on the EED is the magnetic field strength, which affected the EED predominantly at energies less than 100 keV. The effects of the microwave power and frequency, ranging from 100 to 600 W and 11 to 14 GHz, respectively, on the EED were found to be less significant. The presented technique and experiments enable the comparison between direct measurement of the EED and results derived from Bremsstrahlung diagnostics, the latter being severely complicated by the non-Maxwellian nature of the EED reported here. The role of RF pitch angle scattering on electron losses and the relation between the EED of the axially escaping electrons and the EED of the confined electrons are discussed.